The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/en12173212
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Brexit: Implications for the Electricity System of Great Britain

Abstract: The UK’s exit from the European Union (EU) has potential ramifications for the country’s electricity sector, given its increasing interlinkage with other EU electricity systems. Brexit could hamper the development toward higher market integration and the realization of new interconnector projects. Moreover, a fall in the value of the Pound, resulting from Brexit in the medium term, could also affect the electricity trading structure. Combining a European electricity market model and a multi-criteria decision a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Lin and Li ( 2015 ) applied VAC-MGARCH approach to study the spillover effects across natural gas and concluded that oil and natural gas markets are co-integrated across the European market within the first and second moments. The information transmission is expected to have multiple possible impact on the energy integration including the availability and cost of finance, energy market and security of supply, nuclear power, and supply chain of all energy markets across Europe and energy efficiency policy (Egan 2019 ; Mayer et al 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lin and Li ( 2015 ) applied VAC-MGARCH approach to study the spillover effects across natural gas and concluded that oil and natural gas markets are co-integrated across the European market within the first and second moments. The information transmission is expected to have multiple possible impact on the energy integration including the availability and cost of finance, energy market and security of supply, nuclear power, and supply chain of all energy markets across Europe and energy efficiency policy (Egan 2019 ; Mayer et al 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These interconnectors usually provide valuable services to the UK's electricity network by managing intermittent RESs. In the case of a Brexit agreement that does not involve electricity market integration or interconnector share, there is a significant need for ES and other flexibility options to mitigate RESs intermittency [109]. Therefore, it seems that Brexit can raise the deployment of ES devices in the UK.…”
Section: Summary and Brexit Discussionmentioning
confidence: 99%
“…The additional carbon tax on electricity production in the UK still distorts cross border trade in electricity. Mayer et al (2019) model the potential impact of Brexit on electricity as a combination of a devaluation, a reduction of interconnector capacity and higher carbon prices. With high renewables, high carbon prices and no reduction in interconnector capacity Brexit could be positive for consumer welfare, however with reduced interconnector capacity and less domestic renewables production it could be quite negative for consumer welfare (up to an 8bn Euros loss) by 2030.…”
Section: The Effect Of Brexit On the Uk Electricity Systemmentioning
confidence: 99%